Fenomena Social Climber pada Remaja - Giskha Oktaviani Khairun Nisaa; Nadia Aulia Nadhirah (Journal of Education and Counseling (JECO), 2021)
Being famous and existing is a significant problem for teenagers in search of self-identity. Teenagers often do not want to be competitive and want to show their best in front of their peers. Teenagers have an excellent opportunity to become social climber to survive in a group. A social climber is described as the behaviour of someone who wants to get a higher social status around him. The development of technology, especially social media, is one of the media used by teenagers to become social climbers. The article will discuss the social climber phenomenon in adolescents. The method used in this study is a systematic literature review. Data were obtained from various research or non-research scientific articles and books relevant to the research title. The study results stated that the social climber phenomenon in adolescents is influenced by the rapid development of technology and social media. It can be seen from the habits of teenagers to compete to have the latest gadgets, wear branded goods, hang out culture, and display their best photos on social media.